AL AF’ᾹL AL INJᾹZIYAH LADAY MU’ALLIMAH AL LUGHAH AL ARABIYYAH FI AL TAFᾹ’UL AL SOFFI ASNA’A TA’LIM AL LUGHAH AL ARABIYYAH - Lailatul Qomariyah; Akhmad Sauqi Ahya'; Isniyatun Niswah MZ (STIQ Amuntai, 2023)
Directive Acts are illocution acts a teacher uses to ask the student to do a specific action. This speech act affects the input and output of the language studied. This study aimed to analyze the illocutionary acts used by teachers in learning Arabic at the Al Munawaroh Islamic boarding school, Jombang. This study uses a qualitative method with a case study. The techniques for collecting data are observation with recording and interviews and interactive analysis techniques to analyze data. The results of this study show illocutionary speech acts used in learning Arabic with three functions; 1) The function of commanding by using illocution acts in the form of imperative and declarative; 2) Advise function by using speech acts in the form of imperative mood and fill form of amr; 3) The function of prohibiting by using speech acts in the form of declarative and imperatives. The use of this illocutionary act as a teacher's media provides convenience in the learning process and creates a conducive, communicative, and interactive learning environment.